Controlled size green synthesis of bioactive silver nanoparticles assisted by chitosan and its derivatives and their application in biofilm preparation. (15th May 2020) - Affes, Sawsan; Maalej, Hana; Aranaz, Inmaculada; Kchaou, Hela; Acosta, Niuris; Heras, Ángeles; Nasri, Moncef
Graphical abstract: Highlights: AgNPs assisted by chitosan and different Mw-CDP were produced and characterized. AgNPs properties depend on polymer physicochemical characteristics. Chitosan/nanoparticles blend films were developed and characterized. The biological activities of AgNPs and films were investigated. AgNPs size strongly affects films physicochemical and biological properties. Abstract: The aim of this work was to explore the effect of various molecular weight (Mw ) chitosan depolymerization products (CDP) on the silver nanoparticles (AgNPs) and chitosan/AgNPs blend films production. Produced AgNPs, stable during 30 days in a colloïdal form, were characterized in terms of UV–vis, transmission electron microscopy (TEM), dynamic light scattering (DLS) and fourier transform infrared spectroscopy (FTIR) analyses. AgNPs displayed interesting antibacterial and antioxidant properties that were affected by the physicochemical properties of used chitosans. Interestingly, CDP may be used for the preparation of bioactive and stable AgNPs. Additionally, chitosan/AgNPs blend films were prepared and characterized in terms of physiochemical and biological properties. As compared to the chitosan film, various properties were enhanced in the chitosan/AgNPs blend films, including light barrier, opacity, elongation at break, as well as bioactivities, thus suggesting that films could be used as novel alternative food packaging applications.